2014
DOI: 10.1007/s00268-014-2689-6
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Incisional Hernia After Renal Transplantation: A Comparative Study

Abstract: Mesh graft repair is feasible in patients with LIH after renal transplantation. Postoperative complications and recurrences were not more frequent in renal transplantation patients than in those without renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…A recent meta‐analysis 114 demonstrated that hernia repair using a prosthetic mesh is associated with a significant reduction in recurrence compared to primary closure alone. This was confirmed even in the transplant population, where the recurrence rate of 4–33% 7,30–32,115,116 is comparable to that observed in the nontransplant population 18,108 . Chang et al., 32 among 42 kidney and pancreas recipients treated for IH, found an overall recurrence rate of 33%; the recurrence rate was higher in patients treated with primary suture repair (46.6%) than in those treated with mesh repair (29.1%) or with the component separation technique (0%).…”
Section: Treatment Of Abdominal Wall Complicationsmentioning
confidence: 65%
See 3 more Smart Citations
“…A recent meta‐analysis 114 demonstrated that hernia repair using a prosthetic mesh is associated with a significant reduction in recurrence compared to primary closure alone. This was confirmed even in the transplant population, where the recurrence rate of 4–33% 7,30–32,115,116 is comparable to that observed in the nontransplant population 18,108 . Chang et al., 32 among 42 kidney and pancreas recipients treated for IH, found an overall recurrence rate of 33%; the recurrence rate was higher in patients treated with primary suture repair (46.6%) than in those treated with mesh repair (29.1%) or with the component separation technique (0%).…”
Section: Treatment Of Abdominal Wall Complicationsmentioning
confidence: 65%
“…Although mesh repair is potentially the best option for IH repair in kidney transplant recipients, it may expose, in principle, the patient to an increased risk of infection. However, recent studies demonstrated that IH repair with mesh is associated with a low risk of postoperative infections and complications, 88,109,117,122 with an incidence similar to that observed in the general population, 18,30,31 with an overall morbidity and recurrence rate comparable to that observed in the nontransplant population 18,30,31 …”
Section: Treatment Of Abdominal Wall Complicationsmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, due to the rarity of such surgical condition, no standardized technique can be suggested. Several approaches have been described in the literature and, in the minimally invasive era, the laparoscopic repair with mesh placement whether intraperitoneal or preperitoneal seems to represent a valid treatment option [2,9,10,[16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%